The Effect of Different Extrinsic Lubricates on Frictional Resistance Between the Orthodontic Bracket and Archwire: an in vitro study (Mustansiria Dental Journal, 2022)
Aim of the study: The purpose of this research was to investigate how the static and kinetic friction between the orthodontic bracket and archwire will be affected by artificial saliva (AS), oil-containing mouthwash (TTO), and olive oil (OO).Materials and methods: On an Instron universal testing machine with a load cell of 10N and a speed of 2 mm/min. Thirty premolar brackets with 0.019 x 0.025inch stainless steel archwires were assessed. The samples were allocated into three groups randomly. Ten test units were immersed in artificial saliva AS (control group), Tea tree oil mouthwash TTO, and olive oil OO (study groups) for 90 minutes at room temperature. Each test unit is evaluated once only. Statistical analysis used was the ANOVA and Post Hoc LSD tests for parametric tests, the Kruskal-Wallis test, and the Pairwise Comparison test for non-parametric tests.Results: The samples immersed in olive oil significantly showed increased static and kinetic frictional resistance (p= 0.009 and 0.001, respectively), and the TTO showed the least static and kinetic frictional resistance.Conclusion: The 90-minute immersion in oil-containing mouthwash reduced static and kinetic frictional resistance between the orthodontic brackets and archwires, while olive oil (OO) significantly increased them. Based on these findings, oil-containing mouthwash can be prescribed as an excellent prophylactic agent for orthodontic patients. However, the OO is not recommended during the sliding mechanics.